An efficient and diastereoselective synthesis of hydrazino amides via a novel one-pot three-component reaction - Ramezanpour, Sorour; Balalaie, Saeed; Rominger, Frank; Bijanzadeh, Hamid Reza (Tetrahedron, 2013)
An efficient one-pot three-component synthesis of a series of α-hydrazino amides, obtained in high diastereoselectivity and yield, was realized starting from cyclic ketones, hydrazides, and isocyanides in the presence of 10 mol % p-TsOH in ethanol at room temperature. The synthetic protocol was optimized and the observed diastereoselectivity was measured using 1H NMR spectroscopy.
Gesehen am 14.12.2021